Experimental determination of high energy density lithium nitrate hydrate eutectics. (1st August 2022) - Ahmed, Sophia; Hoe, Alison; Alamo, Fabiola; Turner, Nathan; Shamberger, Patrick J.
Abstract: Congruently melting salt hydrates absorb and release heat reversibly upon melting and solidification, and have among the highest energy density and thermal conductivity of low melting point (<50 °C) phase change materials. However, very few salt hydrate systems have been identified that congruently melt near room temperature, which limits their utility in environmental control applications. Here we present thermochemical and thermophysical properties of three near-room temperature ternary eutectic salt hydrate systems based on lithium nitrate trihydrate with high specific energy densities: LiNO3 ·3(H2 O)-LiNO3 -MgNO3 ·6(H2 O) ( T eu  = 25.3 ± 0.3 °C; Δ H eu  = 249 ± 9 J·g −1 ), LiNO3 ·3(H2 O)-LiNO3 -NaNO3 ( T eu  = 25.8 ± 0.5 °C; Δ H eu  = 285 ± 15 J·g −1 ), and LiNO3 ·3(H2 O)-LiNO3 -Zn (NO3 )2 ·6(H2 O) ( T eu  = 13.4 ± 0.5 °C; Δ H eu  = 197 ± 11 J·g −1 ). Thermal conductivity of the liquid LiNO3 ·3(H2 O)-LiNO3 -NaNO3 ternary eutectic is k /W·m −1 ·°C −1  = 0.498 + 0.000523 × T/°C over the temperature range 25 to 65 °C. Finally, we report undercooling in the presence of multiple nucleation agents in the LiNO3 ·3(H2 O)-LiNO3 -NaNO3 eutectic, and demonstrate the effectiveness of including multiple nucleation agents to nucleate the three phases, which solidify simultaneously in these ternary eutectics. Isothermal solidification data, as well as aging of salt hydrates together with nucleation agents for up to 100 days demonstrate that this is a robust and stable system. Highlights: Experimental demonstration of three new phase change materials with among the highest energy densities reported. Thermophysical properties and thermal conductivity reported for select eutectic nitrate hydrate systems. Identification of primary and secondary phase-specific nucleation agents for stable repeatable solidification. Complete characterization of nucleation rates based on kinetic data.